Seismic Passive Control of Cable-Stayed Bridges - Hosam-Eddin M. Ali; Ahmed M. Abdel-Ghaffar (Shock and Vibration)
A three-dimensional modeling procedure is proposed for cable-stayed bridges with rubber, steel, and lead energy dissipation devices. The passive control technique is investigated by considering the response of bridge models with and without energy dissipation devices. The impact of various design parameters on the seismic response of current and future bridge designs is studied. Appropriate locations and properties of the passive devices can achieve better performance for cable-stayed bridges by balancing the significant reduction in earthquake-induced forces against tolerable displacements. Proper design of passive systems can help provide solutions for retro-fitting some existing bridges.